KEMAMPUAN ARUS KAS, LABA DITAMBAH DEPRESIASI DAN MODAL KERJA OPERASIONAL DALAM MEMPREDIKSI ARUS KAS OPERASI MASA DEPAN (Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2010-2014) - Intan Permata Sari, 12.05.52.0029; Sunarto, Sunarto (Students' Journal of Accounting and Banking, 2016)
The purpose of this research is to examine and to provide empirical evidence about how strong the influence of operational cash Flows, net earnings plus depreciation and operational working Capital which are parts of aggregrate earnings, to predict future operating cash flows at manufacturing companies. Components used in this research as independent variable are operational cash Flows, net earnings plus depreciation and operational working Capital. The type of used data for this research are secondary data from annual report manufacturing companies listed on BEI during the period 2010-2014. Sampling method of this research was done by purposive sampling as many as 136 manufacturing companies. This research using a multiple regression models. The results of this research showed that operating cash flows, and net earnings plus depreciation have significant effect on future operating cash flow present have greater predictive capacity than earnings, but variable are operational working capital have not significant effect on future operating cash flow.Keywords: Operational Cash Flow, Net Earnings Plus Depreciation, Operational Working Capital